Improvement of the mechanical consistometers for paper pulp - Romaniuk, Oleksandr; Kril, Bohdan; Kril, Oleksandr (Видавництво Львівської політехніки, 2017)
he purpose of this work is to improve the rotational and blade type mechanical paper pulp consistometers for enhancement of their metering characteristics and reducing the influence of pulp flow velocity, friction torques in shaft sealing and bearings on the measured pulp consistency. These goals are achieved by algorithmic control of the sensor motion velocity and algorithmic processing of measured data. The designs of upgraded rotational and blade consistometers are presented.
Keywords: paper pulp consistency measurements; viscosity; rotational consistometer; blade viscometer; paper stock; non- Newtonian liquids; magnetoelectric transducers